Regulating Bankruptcy: Public Choice, Ideology, & Beyond - A. Mechele Dickerson (Washington University Law Review, 2006)
For almost a decade, members of Congress fiercely debated legislation that would make it harder for people to discharge their debts in bankruptcy. The legislation was finally enacted on April 20, 2005, when the Bankruptcy Abuse Prevention and Consumer Protection Act of 2005 (“BAPCPA”) was signed into law. BAPCPA became fully effective for cases filed on or after October 17, 2005. At one of the earliest hearings on the proposed bankruptcy legislation, one of the bill’s sponsors suggested that “it is probably incorrect to suggest this is a credit card versus consumer problem.” Yet throughout Congressional debates on the legislation, and even after BAPCPA was enacted, many argued that BAPCPA was written by, bought, and paid for by the consumer credit industry, especially the credit card industry. Given the vast sums the consumer credit industry contributed both to individual members and political action committees, it is understandable that many used public choice theory—i.e., the application of microeconomic assumptions to help explain how public officials make decisions—to critique the BAPCPA legislative process. This Article presents a fuller, more nuanced BAPCPA story that is designed to debunk the notion that the BAPCPA legislative process is simply the triumph of one powerful interest group—the credit card lobby—over a weaker group—consumer debtors. Part I of the Article describes BAPCPA’s history and the role that the consumer credit lobby played in getting, then keeping, bankruptcy bills before Congress. In generally describing the legislative process, this Part notes that, notwithstanding fierce debates, opponents and supporters of the legislation agreed on a number of key factual matters relating to the bankruptcy “crisis.” This Part notes, though, that legislators disagreed over other core issues, including what people should do to avoid becoming overindebted and what they should do once they are too far in debt. Part II briefly describes public choice theory and explains the appeal of using this theory to explain the bankruptcy reform legislative process. This Part suggests that public choice theory was most often used to explain why Congress passed BAPCPA because the consumer credit industry made such significant campaign and political action committee contributions while past, current, and future individual debtors failed to organize and lobby against the bankruptcy legislation. Part III shows how, over the course of the legislative process, legislators considered the interests of other powerful groups, notably women, retirees, and veterans. This Part stresses that members of Congress agreed on a number of amendments to the bankruptcy legislation to protect these constituents’ interests. Ultimately, this caused Congress to amend BAPCPA in ways that harmed the interests of the consumer credit lobby. While conceding the difficulties in defining the word “ideology” and the additional difficulty of precisely measuring whether a legislator’s ideology influenced a vote on any given bill, Part IV briefly discusses the role that ideology appeared to play in the legislative process. This Part argues that some relevant ideological issues (such as how people reasonably should be expected to govern their personal finances) and other ideological issues that were raised but were at best only tangentially relevant (such as abortion and minimum wage) played crucial roles in shaping the text of the bankruptcy legislation. Part V argues that the single industry capture story is incomplete and that BAPCPA’s legislative process can best be understood as one that required legislators to balance several interests. On one side is legislators’ desire to continue to receive financial support from the consumer credit lobby; this is balanced against their individual worldviews and philosophy toward “personal responsibility” and their desire to avoid alienating large blocs of politically influential voters
Keywords: Credit cards; Default (Finance); Bankruptcy reform; Regulatory capture; Public choice theory; Ideology; Consumer credit; Legislative process; Lobbying; Bankruptcy Abuse Prevention and Consumer Protection Act of 2005; United States